Evaluating and comparing the effect of zeolite, micro-silica, and fly ash on the mechanical properties of recycled concrete made of 100% recycled aggregates - Seyed Fathollah Sajedi (Iranian Society of Structrual Engineering (ISSE), 2019)
Today, restrictions on access to natural aggregate resources in concrete production have become one of the problems in many countries. Concrete, as one of the most widely used human products, is a factor in consuming a large amount of aggregate. To meet this need, today many developed countries use different types of recycled aggregates as a suitable alternative to natural aggregates. The present study investigates the effect of complete replacement of recycled concrete coils instead of coarse natural aggregates in concrete. In order to improve the quality of recycled concrete, the pozzolans like as micro-silica, natural zeolite and fly ash were used in different percentages. In order to determine and compare the mechanical properties of concrete, 11 mixing designs were made and compressive strength tests at 7, 28 and 91 days, indirect tensile strength (SPT), modulus of elasticity and ultrasound velocity tests at 28 days of age were performed. The results showed that micro-silica, especially at the 10% replacement level, has a dramatic effect on the improvement of the compressive strength of fully recycled concrete compared to other pozzolans. The results of the application of natural zeolite in fully recycled concrete showed that this pozzolan, especially in the 10% substitution, act as a cementitious reducing agent and play a lesser role in improving the mechanical properties of recycled concrete compared to recycled concrete without pozzolan. On the other hand, pozzolanic materials, in a way that improves the compressive strength of recycled concrete, are not able to improve the tensile strength and the modulus of elasticity of the recycled concrete compared to conventional concrete.